(untitled) (Global Journal of Science Frontier Research, 2018)
Ficus rumphii Blume (Family: Moraceae), commonly known as “Gaiaswat” or “Pakar”, is widely used in Bangladeshi traditional medicine to treat various diseases including asthma, kill worms and in snake bite1. The present study was undertaken to separate the solution that is responsible for the antimicrobial agents whom we will further research later.